Statistical Analysis of Salman Taseer and Mumtaz Qadri Case Coverage in Daily Express and Daily The Nation - Muhammad Osama Shafiq ,; Fatima Kiran, (Journal of Basic & Applied Sciences, 2018)
Mumtaz Qadri sentenced to death and Salman Taseer’s assassination were one of the conflicting religious issues of the country. In such conflicting environment dissemination of news through media has strong social and cultural influence on society. Daily express and Daily The Nation portrayed both issues with different angles and perceptions. This study relied upon method of content analysis of the two well-known Pakistani newspapers Daily Express and Daily The Nation. In this study researcher analyzed sixty two editions of the selected newspaper. The result of the study shows imbalance coverage on Salman Taseer and Mumtaz Qadri’s cases. Daily Express and Daily The Nation covered inadequately both the issues of religious tension that fuel more religious tension in the country and the nation is still curious between right and wrong. Both the newspapers have severely underestimated the severity of Mumtaz Qadri and Salman Taseer’s issue.